APOBEC3G genotypes and proviral DNA hypermutations on HIV/AIDS disease progression in Thai and Cambodian children - Torsak Bunupuradah (2018)
© 2015 Future Medicine Ltd. Aim: To evaluate the effect of APOBEC3G host factor on HIV/AIDS progression in perinatally HIV-infected Thai and Cambodian children with distinct clinical patterns; rapid progressors (RPs) and long-term nonprogressors (LTNPs). Materials & methods: APOBEC3G genotypes were determined by polymerase chain reaction-restriction fragment length polymorphism in DNA samples. APOBEC3G-mediated G-to-A hypermutations were analyzed by sequencing of the vif/vpu genes from proviral DNA. Results: Frequency of APOBEC3G 186H/R genotypes, AA:AG:GG, in the RPs was 100:0:0% and 83:17:0% (p = 0.3) in LTNPs. Hypermutation of the vif-coding region was observed in none of the RPs and 8.3% of LTNPs (p = 0.5). Hypermutations at the vpu genes were not detected in either groups' proviral DNA. Conclusion: We observed no significant association of APOBEC3G genotypes and hypermutation rates between children with different profiles of HIV/AIDS disease progression.